EKSPRESI DIRI TENTANG GANGGUAN KECEMASAN SEBAGAI IDE PENCIPTAAN KARYA SENI LUKIS - Layli Kurniawanti; Hamzah; Armennazarudin (Kirana Publisher, 2026)
ABSTRACT The increasing phenomenon of anxiety disorders in modern life due to social pressures, demands of expectations, technological developments, and environmental conditions can affect an individual's mental health. Anxiety disorders are psychological conditions characterized by excessive fear, worry, and anxiety that impact a person's emotional state, thought patterns, and social life. Starting from personal experiences and observations of the surrounding environment, the artist uses anxiety disorders as a source of ideas in creating paintings as a form of self-expression and a medium of visual communication. The purpose of creating this work is to realize self-expression about anxiety disorders in a surrealist style painting, exploring visual elements as a representation of psychological conditions, and producing a work that has aesthetic and communicative value. The creative method used refers to the S.P. Gustami method which consists of the stages of exploration, design, and realization. The exploration stage is carried out through literature studies, environmental observations, emotional experiences, and the collection of visual references. The design stage is realized through visual strategies and the creation of alternative sketches, while the realization stage is carried out by providing materials, mounting the canvas, and the painting process. This work uses a plaque technique with acrylic paint on canvas. The visual elements and principles contained in this painting. The resulting work presents a surrealist painting featuring female figures, symbolic objects, distortions, and transformations of form.